Evaluation Ofantihyperlipidemic Activity Of Ethanolic Extract Of Saussurae Lappa In Rats - J. ANBU,; ASHWINI ANJANA,; K. PURUSHOTHAMAN,; M. SUMITHRA,; S. SUGANYA,; NAVEEN KUMAR BATHULA,; SHANTANU MODAK, (International Journal of Pharma and Bio Sciences, 2011)
Hyperlipidemia is an excess of fatty material called lipids, largely cholesterol and triglycerides, in the blood. The main aim of treatment in patients with hyperlipidemia is to reduce the risk of developing ischemic heart disease or the occurrence of further cardiovascular or cerebrovascular disease. The aim of the study is to reduce the levels of triglycerides by using herbal plant ethanolic extract of Saussurae Lappa (EESL). The food intake and body weight was increased in high cholesterol fed diet rats as compared to normal control. Treatment with ethanolic extract of Saussurae Lappa showed no change in food intake but there was significant decrease in weight gain as compared to high cholesterol fed diet rats. The antihyperlipidemic activity may be due to presence of tannins, triterpenes, alkaloids, inulin, essential oil present in the roots of Saussurae Lappa.